Diagnosis and treatment of clinically amyopathic dermatomyositis (CADM): a case series and literature review. Issue 8 (August 2016) - Gil, Bornstein; Merav, Lidar; Pnina, Langevitz; Chagai, Grossman
Abstract The objective of this study was to report the clinical course of a cohort of patients with clinically amyopathic dermatomyositis (CADM) in correlation to the presence or absence of anti-melanoma differentiation-associated gene 5 (MDA-5) antibody. Five patients with CADM presented to our rheumatology unit between September 1, 2011 and March 31, 2014. We hereby present their clinical course, laboratory findings, imaging modalities, functional tests, and treatments regimens. Our cohort included five patients, with a mean age of 41.8 ± 17.7. Three patients, all anti-MDA-5 antibody positive, developed rapidly progressive interstitial lung disease (ILD) within 4.3 ± 4.5 months of presentation. Two of these patients succumbed to their disease within 30 months of diagnosis despite intensive immunosuppressive therapy. The third anti-MDA-5-positive patient with ILD is still stable, 20 months from disease onset, on massive combination therapy. One patient developed CADM associated with the anti-p155/140 antibody, a year after completing chemotherapy for non-seminomatous germ cell tumor. He presented with a benign clinical course with no evidence of ILD and no recurrence of malignancy after 20 months of follow-up. The fifth patient in our cohort, who is anti-MDA-5 negative and has no evidence of malignancy, also enjoys a benign clinical course. The presence of anti-MDA-5 antibodies in CADM patients is associated with rapidly progressive ILD and a poor prognosis. The serologic profile of patients with CADM should be routinely evaluated and integrated with clinical data in the management of these patients.